Mitos Penciptaan pada Serat Purwakandha Brantakusuman dan Potensi Kajian Filsafatnya - Sartini Sartini; Luwiyanto Luwiyanto (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2020)
This article examines the creation myth in Serat Purwakandha Brantakusuman (SPB), how its characteristics are compared to myths in Indonesia and existing mythical theories, and explains philosophical themes that can be examined from these myths in order to give its theoretical contributions in existing mythical theories. It is a literature study by reviewing books texts, research reports, journals, and other sources. The analysis is done by interpretation, coherence-holistic, description, and analysis-synthesis. The theoretical framework used is the myth theory C A. Van Peursen and Clifford Geertz. The results of the study indicate that the myth of the creation of plants in SPB is based on the story of the death of Dewi Tisnawati who was banished to earth. The study of myths about the origin of plants is new because research examining myths related to agriculture and Dewi Sri, the influence of myths in life and human activities, forms of rituals and socio-cultural activities, and the relationship between myths and art, are more related to origin place. The myths in SPB and myths in Indonesia contribute to supporting myth concepts that have been described by great thinkers. The creation myth and other myths in the SPB can be subject to study from the perspective of the branches of philosophy and its conceptual substances can also be criticized philosophically